Isolation, quarantine, social distancing and community containment: pivotal role for old-style public health measures in the novel coronavirus (2019-nCoV) outbreak - Wilder-Smith, Annelies; Freedman, David O. (Journal of travel medicine, 2020)
Public health measures were decisive in controlling the SARS epidemic in 2003. Isolation is the separation of ill persons from non-infected persons. Quarantine
Gesehen am 08.06.2020